Total synthesis of pyrrolo[2,3-c]quinoline alkaloid: trigonoine B - Nishiyama, Takashi; Hamada, Erina; Ishii, Daishi; Kihara, Yuuto; Choshi, Nanase; Nakanishi, Natsumi; Murakami, Mari; Taninaka, Kimiko; Hatae, Noriyuki; Choshi, Tominari (Beilstein Journal of Organic Chemistry, 2021)
The first total synthesis of the pyrrolo[2,3-c]quinoline alkaloid trigonoine B (1) was accomplished via a six-step sequence involving the construction of an N-substituted 4-aminopyrrolo[2,3-c]quinoline framework via electrocyclization of 2-(pyrrol-3-yl)benzene containing a carbodiimide moiety as a 2-azahexatriene system. The employed six-step sequence afforded trigonoine B (1) in 9.2% overall yield. The described route could be employed for the preparation of various N-substituted 4-aminopyrroloquinolines with various biological activities.
Keywords: 2-azahexatiriene system; carbodiimide; electrocyclization; pyrrolo[2,3-c]quinoline; trigonoine B